Distribution and prevalence of races of Puccinia graminis tritici in Brazil in 1971 - Coelho, Elisa Thomaz; Barcellos, Amarilis Lares (Pesquisa Agropecuaria Brasileira, 2014)
To continue the survey of races samples of Puccinia graminis Pers. f. sp. tritici Ericks & E. Henn were collected in the Brazilian wheat region in 1971. Races 11, 11/65, 15/65, 15/71, 17, 17/61 and 17/63 were identified on 159 stem rust samples. Race 15/65 was prevalent, reaching more than 40% of the samples. Races 17/63 and 17, second and third in order of prevalence, comprised about 20 and 19% of the samples, respectively. The combination of the genes Sr 7 and Sr 11 continues to confer resistance to all occurrent races.